Status kesuburan tanah, aplikasi pupuk petroganik + NPK terhadap pertumbuhan jagung pulut merah genotipe Unipa di Distrik Waibu Kabupaten Jayapura - Datu L. Palulun; Irnanda A. F. Djuuna; Purbokurniawan Purbokurniawan; Alce Ilona Noya; Nouke L. Mawikere (Program Pascasarjana Universitas Papua, 2023)
Soil fertility status was an important factor that determines the success of corn farming. The five properties used to predict this fertility status are C-Organic, KB, P2O5 – total, K2O – total, and CEC. The combination of the use of organic and inorganic fertilizers aims to improve soil fertility, increase productivity, and soil sustainability. The study used a 2-factor randomized block design. The first factor was the combination of fertilization consisted of 6 levels and the second factor was 2 genotypes of red corn pulut Unipa. The results showed that the soil fertility status at the study site was classified as low with the details of the criteria of C-Organic (Low), KB (High), P2O5 (High), K2O (High), and CEC (Low). There were no interaction in all growth components. The genotype of Anggi Merah Pulut Unipa 3 had better growth than Anggi Merah Pulut Unipa 1.